Tanggung Jawab Hukum Penilai Publik Untuk Ganti Kerugian Dalam Pengadaan Tanah Bagi Kepentingan Umum Yang Berkepastian Hukum - Ummi Habsyah; Hartana Hartana; Dewi Iryani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Land has an economic value to its owner. When land is acquired in the public interest, the loss is determined by the KJPP Land Appraiser, who is responsible for the appraisal. Violations of the appraiser's duties are subject to administrative and/or criminal sanctions. The valuation includes land, surface and underground areas, buildings, equipment and related objects. The results of the appraisal become the basis for deliberations to determine the compensation, and the entitled party may take legal action in case of disagreement. This research uses a normative juridical method with a Legislation, Case, and Concept approach. The data used are secondary data (primary, secondary, and tertiary legal materials) and primary data as support. Data analysis is carried out using the normative juridical analysis method. The results of the study show that there are several problems in land acquisition, such as different results of object value assessment and regulatory inconsistencies, which lead to unequal bargaining positions. Conclusion: Appraisers are responsible for conducting appraisals according to established procedures. Researchers hope that the valuation results can be accounted for and in accordance with the law, as well as special rules for the Public Appraisal Profession and Supreme Court Regulations related to compensation procedures in land acquisition.